Psihološki vidiki in priprava otroka na zdravstvene posege - Bürger-Lazar, Martina (Slovenska pediatrija, 2010)
Pain is a subjective and complex experience modulated by various biological, psychological and social factors. A child's perception of pain depends on his cognitive development and previous experiences of pain. Medical procedures, especially painful ones, are often stressful for the child. Early experiences of painful medical procedures in childhood play an important role in forming an individual's response to pain both in childhood and adulthood. Recurrent negative experiences of painful medical procedures in childhood may have long-term negative psychological effects. Thus, in addition to pharmacologicalpreparation of the child for medical procedures, it is important to use various psychological approaches and cognitive-behavioural techniques, which are helpful in reducing a child's distress and pain perception. The choice of these must be based not only on the invasiveness andduration of the procedure itself, but on the child's personal characteristics. This requires a great deal of flexibility in the choice of appropriate methods and resources as well as professionally highly trained andsensitive medical and nursing staff.
Keywords: Bolečina; Child; Child Behavior; Cognitive Therapy; otroci; Otrok; Otrok, vedenje; Pain; Predoperativna oskrba; Preoperative Care; psihološki vidik; Psychology; Spoznavno zdravljenje; zdravljenje